Tanshinone IIA Suppresses Proliferation and Inflammatory Cytokine Production of Synovial Fibroblasts from Rheumatoid Arthritis Patients Induced by TNF-α and Attenuates the Inflammatory Response in AIA Mice - Du, Hongyan; Wang, Yuechun; Zeng, Yongchang; Huang, Xiaoming; Liu, Dingfei; Ye, Lvlan; Li, Yang; Chen, Xiaochen; Liu, Tiancai; Li, Hongwei; Wu, Jing; Yu, Qinghong; et al. (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is a chronic and progressive autoimmune disease in which activated RA fibroblast-1ike synoviocytes (RA-FLSs) are one of the main factors responsible for inducing morbidity. Previous reports have shown that RA-FLSs have proliferative features similar to cancer cells, in addition to causing cartilage erosion that eventually causes joint damage. Thus, new therapeutic strategies and drugs that can effectively contain the abnormal hyperplasia of RA-FLSs and restrain RA development are necessary for the treatment of RA. Tanshinone IIA (Tan IIA), one of the main phytochemicals isolated from Salvia miltiorrhiza Bunge, is capable of promoting RA-FLS apoptosis and inhibiting arthritis in an AIA mouse model. In addition, RA patients treated at our clinic with Tan IIA showed significant improvements in their clinical symptoms. However, the details of the molecular mechanism by which Tan IIA effects RA are unknown. To clarify this mechanism, we evaluated the antiproliferative and inhibitory effects of proinflammatory factor production caused by Tan IIA to RA-FLSs. We demonstrated that Tan IIA can restrict the proliferation, migration, and invasion of RA-FLSs in a time- and dose-dependent manner. Moreover, Tan IIA effectively suppressed the increase in mRNA expression of some matrix metalloproteinases and proinflammatory factors induced by TNF-α in RA-FLSs, resulting in inflammatory reactivity inhibition and blocking the destruction of the knee joint. Through the integration of network pharmacology analyses with the experimental data obtained, it is revealed that the effects of Tan IIA on RA can be attributed to its influence on different signaling pathways, including MAPK, AKT/mTOR, HIF-1, and NF-kB. Taken together, these data suggest that the compound Tan IIA has great therapeutic potential for RA treatment.